The Role of Dopamine in the Nucleus Accumbens and Striatum during Sexual Behavior in the Female Rat - Becker, Jill B. (J Neurosci, 2001)
Dopamine in dialysate from the nucleus accumbens (NAcc) increases during sexual and feeding behavior and after administration of drugs of abuse, even those that do not directly activate dopaminergic systems (e.g., morphine or nicotine). These findings and others have led to hypotheses that propose that dopamine is rewarding, predicts that reinforcement will occur, or attributes incentive salience. Examining increases in dopamine in NAcc or striatum during sexual behavior in female rats provides a unique situation to study these relations. This is because, for the female rat, sexual behavior is associated with an increase in NAcc dopamine and conditioned place preference only under certain testing conditions. This experiment was conducted to determine what factors are important for the increase in dopamine in dialysate from NAcc and striatum during sexual behavior in female rats. The factors considered were the number of contacts by the male, the timing of contacts by the male, or the ability of the female to control contacts by the male. The results indicate that increased NAcc dopamine is dependent on the timing of copulatory stimuli, independent of whether the female rat is actively engaged in regulating this timing. For the striatum, the timing of copulatory behavior influences the magnitude of the increase in dopamine in dialysate, but other factors are also involved. We conclude that increased extracellular dopamine in the NAcc and striatum conveys qualitative or interpretive information about the rewarding value of stimuli. Sexual behavior in the female rat is proposed as a model to determine the role of dopamine in motivated behavior.